2017
DOI: 10.21608/adjalexu.2017.57919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Socket Shield Technique for Immediate Implantation

Abstract: INTRODUCTION: Numerous publications have verified that tooth extraction is followed by dimensional changes of the alveolar ridge contour. The resorption of the alveolar ridge is more pronounced on the buccal than on the lingual aspect of the extraction socket. In particular, in the aesthetic zone, the successive soft and hard tissue deficiencies can interfere with optimal implant positioning and hamper the overall aesthetic outcome of implant-supported prostheses. OBJECTIVES: This study was designed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(84 citation statements)
references
References 18 publications
1
78
0
1
Order By: Relevance
“…Baumer et al, 20 in 2015, reported a mean of 1 mm horizontal loss after final restoration. Baumer et al, 14 in 2017, reported that the marginal bone loss changes at the mesial and distal aspects were 0.33 and 0.17 mm, respectively, and Barakat et al, 21 in 2017, reported that the mean horizontal bone loss after 7 months was 0.10 ± 0.03 mm while the mean vertical bone loss after 7 months was 0.44 ± 0.24 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Baumer et al, 20 in 2015, reported a mean of 1 mm horizontal loss after final restoration. Baumer et al, 14 in 2017, reported that the marginal bone loss changes at the mesial and distal aspects were 0.33 and 0.17 mm, respectively, and Barakat et al, 21 in 2017, reported that the mean horizontal bone loss after 7 months was 0.10 ± 0.03 mm while the mean vertical bone loss after 7 months was 0.44 ± 0.24 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Siormpas et al 4 further added that the socket shield increases the durability of the implant service by preserving their surrounding tissues. Also, Barakat et al 5 found that this technique maintained the buccal bone plate, and Mitsias et al 6 The third generation bioactive glass, calcium phosphosilicate, utilized in this study was proven to result in vital bone formation after a 4 to 5 months healing period and tended to increase over time as found by Kesmas et al, 15 Kotsakis et al, 17,18 and Gonshor et al 19 who reported that this relatively fast healing may provide a clinical advantage for implant osseointegration. In addition, the findings of Bembi et al 20 revealed that the bioactive calcium phosphosilicate was biocompatible and safe to use without causing any inadvertent tissue response or antigenic reaction for the treatment of intra bony defects once good oral hygiene and inflammationfree periodontal tissue were maintained in the postoperative phase.…”
Section: Discussionmentioning
confidence: 97%
“…However, some histologic evidence documented loss of bone, formation of cementum and fibrous tissue between the implant surfaces and the shield. [1][2][3][4][5] Other studies were in favor of the socket shield, documenting successful distance and contact osteogenesis, despite an almost half centimeter space from the implant to the socket shield with no bone grafting or membrane assistance, and maintenance of the labial plate of bone as if no tooth extraction took place. [6][7][8] Although, there are no determining guidelines in regards to the type of biomaterials, or surgical techniques used, an atraumatic extraction technique and a suitable bone graft material, can efficiently reduce vertical and horizontal bone resorption after teeth extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preserving and maintaining the bone anatomy and soft tissue architecture in the anterior region is essential for maintaining esthetics in implant-supported restorations [ 5 ]. Different techniques and materials have been proposed to prevent the bone resorption; however, immediate dental implant placement and alveolar preservation procedures have been recommended [ 6 ]. Osseointegration has been defined as a direct and functional connection between bone and an artificial implant.…”
Section: Introductionmentioning
confidence: 99%
“…The socket-shield technique has shown a success rate of 96.5% [ 2 ]; however, teeth affected by periodontal disease, vertical or horizontal root fractures under the bone ridge, and internal root resorption can influence the prognosis after the placement of the dental implant and require further research [ 5 ]. In addition, the following clinical complications have been associated with the socket-shield technique: a lack of osteointegration of the dental implant, infections, and the mobilization, migration, and resorption of the root fragment [ 6 ]. An acceptable pink esthetic around the dental implant is generally demanded by the patient.…”
Section: Introductionmentioning
confidence: 99%